Method for preparing aluminum-fluorine co-doped positive electrode material from nickel-cobalt-manganese waste battery positive electrode material
By mixing the cathode sheet of nickel-cobalt-manganese waste battery with lithium source and baking to prepare aluminum-fluorine co-doped cathode material, the problem of low transformation failure and recycling efficiency of the cathode material in the existing recycling methods is solved, and the stability of the material and the improvement of circulation performance are achieved.
Patent Information
- Application Number
- CN202411737171.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
AI Technical Summary
The existing method of recycling the cathode material of nickel-cobalt-manganese waste batteries requires transformation and destruction of the cathode material, making it difficult to recycle the cathode material in its original active form, and the recycling efficiency is not high, and there are problems of environmental pollution and poor economic benefits.
The positive electrode sheet of nickel-cobalt-manganese waste battery is mixed with a lithium source to obtain a composite powder and calcined under a protective atmosphere to prepare an aluminum-fluorine co-doped positive electrode material. This method does not require separation of aluminum foil from the positive electrode material, nor does it require removal of PVDF adhesive. The process is simple and the aluminum foil and PVDF in the positive electrode sheet can be effectively utilized.
The stability of ternary lithium positive electrode materials has been improved, the capacity loss during material circulation is reduced, the recycling performance of materials is improved, and the recycling process is simplified, reducing environmental pollution and costs.
Smart Images

Figure CN119551740A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for recycling positive electrode materials of nickel-cobalt-manganese waste batteries, and in particular to a method for preparing aluminum-fluorine co-doped positive electrode materials by utilizing positive electrode materials of nickel-cobalt-manganese waste batteries, and belongs to the field of waste battery recycling. Background Art
[0002] As people's demand for electronic products such as mobile phones and electric vehicles increases, the output of lithium-ion batteries increases year by year. Since the life of lithium-ion batteries is generally 3 to 8 years, a large number of waste batteries will appear in the future. Among all lithium-ion battery positive electrode materials, the energy storage density of ternary lithium materials (200WH / kg) is nearly twice that of lithium iron phosphate (90~120WH / kg), which is more suitable for the passenger car market's demand for endurance. Therefore, power batteries with ternary lithium as positive electrode materials have been widely used, and the amount of waste lithium-ion batteries has also increased year by year. Since waste lithium-ion batteries contain metals such as nickel, cobalt, manganese, aluminum, copper, and organic solvents such as electrolytes, if reasonable means are not adopted for recycling, it will not only pollute the environment but also waste resources. So far, recycling ternary lithium waste is imperative for reusing materials, saving costs and protecting the environment.
[0003] At present, the ternary recovery mainly adopts chemical methods, which can be specifically divided into hydrometallurgy and pyrometallurgy. Hydrometallurgy mainly separates aluminum foil from positive electrode materials by chemical methods by adding alkali, acid, precipitant, extractant, etc. What is obtained is a precipitate containing positive electrode metal cations, and the ternary positive electrode material is repaired by lithium replenishment. Pyrometallurgy obtains precursor precipitation through high-temperature smelting, electrolytic refining, acid dissolution and precipitation, and the ternary positive electrode material is obtained by lithium replenishment and repair. The chemical recovery method uses acid, alkali and other reagents, which is easy to cause acid, alkali and other pollution, and the environmental problems are prominent. The latter uses high-temperature capacity and electrolytic refining, which is more expensive.
[0004] Most of the existing methods for recycling the positive electrode materials of used nickel-cobalt-manganese batteries require the transformation and destruction of the positive electrode materials, and it is difficult to recycle the positive electrode materials in their original active form. However, the recycling process is incomplete, the recycling efficiency is low, there is a certain degree of damage to the environment, and the economic benefits are poor.
[0005] A Chinese invention patent (CN108103323B) discloses a method for recycling positive electrode materials of waste nickel-cobalt-manganese batteries. The positive electrode sheets need to be treated with organic solvents. There are many steps in the recycling process, and only the activity of the recycled positive electrode materials can be maintained.
[0006] A Chinese invention patent (CN113086996A) discloses a method for recycling waste ternary fluorine-doped battery positive electrode materials. The method includes electrode separation, impurity removal, lithium extraction, acid leaching and proportioning, etc., to prepare ternary precursor materials. The lithium recovery rate is only 95%, and a fluorine-doped ternary lithium positive electrode material is obtained.
[0007] In summary, the existing methods for recycling ternary cathode materials mainly use chemical methods, and the process is roughly to dissolve aluminum foil by adding alkali, filter to obtain cathode materials; and obtain compounds corresponding to metal ions by adding alkali, acid, precipitant, extractant, etc. These methods for recycling cathode materials obtain the raw materials required for their synthesis, which not only destroys the structure, morphology and activity of the original cathode materials, but also has complex processing processes, acid and alkali pollution, and high costs. Summary of the invention
[0008] In order to solve the technical problems of the need to transform ternary materials and complex processes in the recycling of positive electrode materials of existing nickel-cobalt-manganese waste batteries, the purpose of the present invention is to provide a method for preparing aluminum-fluorine co-doped positive electrode materials using positive electrode materials of nickel-cobalt-manganese waste batteries. The method does not require separation of aluminum foil and positive electrode materials from positive electrode sheets, nor does it require removal of PVDF binder in the positive electrode materials. The process is very simple, and the aluminum foil and PVDF of the positive electrode sheets are effectively utilized as aluminum sources and fluorine sources, respectively, to repair the failed nickel-cobalt-manganese positive electrode materials while realizing doping modification, so as to improve the stability of ternary lithium positive electrode materials, reduce capacity loss during material circulation, and thus improve the material's circulation performance.
[0009] In order to achieve the above technical objectives, the present invention provides a method for preparing an aluminum-fluorine co-doped positive electrode material using a nickel-cobalt-manganese waste battery positive electrode material, the method comprising the following steps:
[0010] 1) mixing and ball-milling the positive electrode sheet obtained by stripping the waste nickel-cobalt-manganese battery with a lithium source to obtain a composite powder; the lithium source comprises lithium hydroxide;
[0011] 2) The composite powder is calcined under a protective atmosphere to obtain an aluminum-fluorine co-doped positive electrode material.
[0012] The key to the technical solution of the present invention is that the failed nickel-cobalt-manganese positive electrode sheet is not subjected to aluminum foil stripping and PVDF removal treatment, but directly uses strongly alkaline LiOH as a lithium source to perform high-temperature repair and doping modification on the failed nickel-cobalt-manganese-lithium positive electrode material. On the one hand, the strong alkalinity of LiOH can promote the degradation of PVDF, and LiOH can react with hydrogen fluoride produced by pyrolysis of PVDF to form lithium fluoride, which can dope and modify nickel-cobalt-manganese-lithium. In addition, LiOH can convert metallic aluminum into lithium aluminate at high temperature, and lithium aluminate is a precursor raw material of aluminum-doped nickel-cobalt-manganese-lithium. Finally, LiOH can also be used as a lithium source to compensate for the loss of lithium source in the ternary lithium battery during the charging and discharging process.
[0013] As a preferred solution, the mass proportion of lithium hydroxide in the lithium source is not less than 50%. The lithium source can adopt the conventional lithium source in the prior art, but it must contain an appropriate amount of lithium hydroxide with strong alkalinity, which can promote the breaking of CF bonds in PVDF, and can capture hydrofluoric acid and convert it into lithium fluoride to dope nickel-cobalt-manganese lithium as a fluorine source. At the same time, LiOH can convert metallic aluminum into lithium aluminate at high temperature, and dope nickel-cobalt-manganese lithium as an aluminum source. In order to better realize the doping modification of nickel-cobalt-manganese lithium positive electrode materials by aluminum and fluorine, the proportion of lithium hydroxide is preferably controlled within a preferred range. For example, if the proportion of lithium hydroxide is too low, the fluorine doping effect will deteriorate. It is further preferred that the mass proportion of lithium hydroxide in the lithium source is not less than 60%. It is further preferred that the mass proportion of lithium hydroxide in the lithium source is not less than 75%.
[0014] As a preferred solution, the mass of the lithium source is 5-10% of the mass of the positive electrode powder. If the mass ratio of the lithium source is too low, the doping modification and repair effects on the failed nickel-cobalt-manganese-lithium positive electrode material will be poor.
[0015] As a preferred solution, the lithium source selectively contains lithium oxide and / or lithium peroxide, specifically Li2O and / or Li2O2. Using lithium oxide and / or lithium peroxide as the lithium source can avoid the introduction of impurities and is conducive to the formation of lithium aluminate.
[0016] As a preferred solution, the conditions for ball milling are: the ball milling medium is water and / or ethanol, the diameter of the grinding beads is 10mm~20mm, the rotation speed is 30~60rmp, the ball-to-material mass ratio is 3:1~8:1, and the ball milling time is 90~180 minutes. During the ball milling process, parameters such as the ball milling rate, ball milling time and grinding bead diameter have an impact on the activity retention and yield of the nickel-cobalt-manganese-lithium positive electrode material. For example, if the diameter of the ball milling beads is too small, although the good activity of the recovered positive electrode material can be maintained, the aluminum foil will not be ground. Even if the ball milling time is extended, the aluminum foil is difficult to grind. Therefore, the preferred grinding bead diameter is 10mm~20mm. Under this preferred grinding bead diameter, the activity of the positive electrode material can be ensured, and the reaction activity of subsequent aluminum doping can be ensured. The grinding beads are preferably zirconia beads. The ball milling speed is preferably 30~60rmp, and the ball-to-material mass ratio is preferably 3:1~8:1. At a lower ball milling speed and a lower ball-to-material ratio, it helps to improve the recovery effect of the positive electrode material and ensure the reaction activity of the positive electrode material. The medium used in ball milling is water and / or ethanol, which can effectively avoid the dissolution loss of lithium elements during wet ball milling and better maintain the activity of the recovered positive electrode material.
[0017] As a preferred solution, the calcination conditions are: in a protective atmosphere, the temperature is raised to 350-400°C at a heating rate of 3-5°C / min, kept warm for 2-5h, then raised to 800-1000°C at 3-5°C / min, kept warm for 10-15h, and cooled with the furnace. During the calcination process, the temperature is first kept at 300-400°C. The effect and purpose is to use the strong alkaline effect of lithium hydroxide at a relatively low temperature to promote the low-temperature degradation of PVDF, avoid the pyrolysis and carbonization of PVDF, and convert LiOH into LiF at this stage; at the same time, LiOH is used to react with aluminum foil to convert into lithium aluminate, and the effect and purpose of keeping at 800-1000°C is to ensure fluorine doping and lithium supplementation in defective nickel-cobalt-manganese-lithium under liquid phase conditions, and to ensure the density of the ternary positive electrode material. In addition, it is very beneficial to co-dope the nickel-cobalt-manganese-lithium positive electrode material with aluminum and fluorine as cations and anions respectively, which improves the structural stability of the nickel-cobalt-manganese-lithium positive electrode material and compensates for the loss of lithium in the nickel-cobalt-manganese-lithium positive electrode material during the battery charging and discharging process.
[0018] As a preferred solution, the protective atmosphere is at least one of nitrogen, argon, and nitrogen and argon.
[0019] The method for preparing an aluminum-fluorine co-doped positive electrode material using a nickel-cobalt-manganese waste battery positive electrode material provided by the present invention comprises the following specific steps:
[0020] 1) Discharge the residual power of the used nickel-cobalt-manganese batteries, disassemble the batteries, separate the positive electrode, negative electrode and separator, and wash and dry the positive electrode;
[0021] 2) The positive electrode sheet is directly mixed with 5-10wt% of LiOH or a mixture of lithium hydroxide and lithium oxide for wet ball milling to obtain a premix; the medium used for ball milling is water and / or ethanol; the diameter of the grinding balls used in the ball milling process is 10mm-20mm; the rotation speed during the ball milling process is 30-60rmp, the ball-to-material mass ratio is 3:1-8:1, and the ball milling time is 90-180 minutes;
[0022] 3) After the premix is ground and mixed evenly, the temperature is raised to 350~400℃ at 3~5℃ / min in a non-oxidizing atmosphere and kept warm for 2~5h; then the temperature is raised to 800~1000℃ at 3~5℃ / min, kept warm for 10~15h, and cooled with the furnace to obtain the aluminum-fluorine co-doped ternary lithium battery positive electrode material;
[0023] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:
[0024] The technical solution of the present invention greatly simplifies the recycling process of waste nickel-cobalt-manganese-lithium positive electrode materials. There is no need to peel off the aluminum foil and the positive electrode material, and it is impossible to remove the PVDF from the organic binder in the positive electrode material. The two can be effectively utilized in the repair process of waste nickel-cobalt-manganese-lithium positive electrode materials, respectively, as aluminum sources and fluorine sources, to repair the failed nickel-cobalt-manganese positive electrode materials while realizing doping modification, so as to improve the stability of the ternary lithium positive electrode material, reduce the capacity loss during the material cycle, and thus improve the material's cycle performance. The aluminum-fluorine co-doped positive electrode material sample prepared by the present invention has an initial discharge capacity of 189.3mAh / g at 0.1C, and a capacity of 180.1mAh / g after 100 cycles. Compared with ternary lithium materials, the cycle performance is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the XRD spectrum of the aluminum-fluorine co-doped ternary lithium prepared in Example 1 of the present invention.
[0026] Figure 2 This is a charge and discharge curve diagram of the aluminum-fluorine co-doped ternary lithium prepared in Example 2 of the present invention.
[0027] Figure 3 This is a cycle performance diagram of the aluminum-fluorine co-doped ternary lithium battery prepared in Example 1 of the present invention.
[0028] Figure 4 This is a charge and discharge curve diagram of the aluminum-fluorine co-doped ternary lithium prepared in Example 3 of the present invention.
[0029] Figure 5 This is a SEM image of the aluminum-fluorine co-doped ternary lithium prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The following specific examples are intended to further illustrate the present invention, rather than to limit the scope of protection of the claims of the present invention.
[0031] The charge and discharge experiments of the assembled batteries were carried out using the Newware CT2001A tester produced by Shenzhen Newware Electronics Co., Ltd.
[0032] The assembled battery was tested by AC impedance spectroscopy using Gamry Instrument's Interface 1010E electrochemical workstation.
[0033] The specific method for obtaining the mixed powder of waste ternary lithium positive electrode and lithium source in the following embodiment is as follows: the waste nickel-cobalt-manganese battery is fully discharged and disassembled by the existing conventional method to obtain the positive electrode sheet. The positive electrode sheet is first crushed and sieved to remove some solid powders that are difficult to crush, and then the lithium source is added for wet ball milling. The medium used for ball milling is ethanol; the diameter of the grinding ball used in the ball milling process is 15mm; the rotation speed during the ball milling process is 50rmp, the ball-to-material mass ratio is 5:1, the ball milling time is 120 minutes, and after ball milling, it is dried, ground, and sieved through a 300-mesh sieve to obtain a mixed powder.
[0034] Example 1
[0035] (1) Take the mixed powder (2.0g waste ternary lithium positive electrode powder + 0.20g LiOH), raise the temperature to 350℃ at 5℃ / min in Ar atmosphere, and keep it for 2h; then raise the temperature to 900℃ at 5℃ / min, keep it for 12h, and cool it in the furnace to obtain aluminum-fluorine co-doped ternary lithium positive electrode material. Its XRD is as follows: Figure 1 As shown, SEM Figure 5 shown.
[0036] (2) Aluminum-fluorine co-doped ternary lithium was used as the positive electrode material of the battery, mixed with conductive black (Super-P) and polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, N-methylpyrrolidone (NMP) was added dropwise, ground into a slurry with a mortar, and the slurry was evenly applied to aluminum foil and dried in a vacuum oven for 12 hours. A button cell was assembled with aluminum foil as the positive electrode and lithium sheet as the negative electrode, and the performance of the battery was tested and compared with that of the battery with NCM811 as the positive electrode material. Figure 3 shown.
[0037] The results show that the first discharge capacity of the aluminum-fluorine co-doped ternary lithium cathode material reaches 189.3mAh / g, which is lower than the first discharge capacity of the battery assembled with NCM811 (193.2mAh / g); the capacity after 100 cycles is 180.1mAh / g, which is higher than the capacity of the battery assembled with NCM811 after 100 cycles (164.3mAh / g). Therefore, the cycle performance of the aluminum-fluorine co-doped ternary lithium cathode material has been improved.
[0038] Example 2
[0039] (1) Take a mixed powder (2.0 g of waste ternary lithium positive electrode powder + 0.15 g of LiOH and 0.05 g of Li2O), raise the temperature to 350°C at 5°C / min in an Ar atmosphere, and keep it warm for 2 h; then raise the temperature to 900°C at 5°C / min, keep it warm for 12 h, and cool it in the furnace to obtain an aluminum-fluorine co-doped ternary lithium positive electrode material.
[0040] (2) Aluminum-fluorine co-doped ternary lithium was used as the positive electrode material of the battery, mixed with conductive black (Super-P) and polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1, N-methylpyrrolidone (NMP) was added dropwise, ground into a slurry with a mortar, and the slurry was evenly applied to aluminum foil and dried in a vacuum oven for 12 hours. A button cell was assembled with aluminum foil as the positive electrode and lithium sheet as the negative electrode, and the battery performance was tested.
[0041] The first charge and discharge curve of aluminum-fluorine co-doped ternary lithium positive electrode material is as follows Figure 2 The results show that the performance of aluminum-fluorine co-doped ternary lithium cathode material is basically consistent with that of NCM811 material.
[0042] Example 3
[0043] (1) Take a mixed powder (2.0g of waste ternary lithium positive electrode powder + 0.15g LiOH and 0.05g Li2O2), raise the temperature to 350℃ at 5℃ / min under Ar atmosphere, and keep it warm for 2h; then raise the temperature to 900℃ at 5℃ / min, keep it warm for 12h, and cool it in the furnace to obtain an aluminum-fluorine co-doped ternary lithium positive electrode material.
[0044] (2) Aluminum-fluorine co-doped ternary lithium was used as the positive electrode material of the battery, mixed with conductive black (Super-P) and polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1, N-methylpyrrolidone (NMP) was added dropwise, ground into a slurry with a mortar, and the slurry was evenly applied to aluminum foil and dried in a vacuum oven for 12 hours. A button cell was assembled with aluminum foil as the positive electrode and lithium sheet as the negative electrode, and the battery performance was tested.
[0045] The first charge and discharge curve of aluminum-fluorine co-doped ternary lithium positive electrode material is as follows Figure 4 The results show that the performance of aluminum-fluorine co-doped ternary lithium cathode material is basically consistent with that of NCM811 material.
[0046] Example 4
[0047] (1) Take a mixed powder (2.0 g of waste ternary lithium positive electrode powder + 0.15 g LiOH, 0.025 g Li2O and 0.025 g Li2O2), and heat it to 350°C at 5°C / min in an Ar atmosphere, and keep it for 2 h; then heat it to 950°C at 5°C / min, keep it for 12 h, and cool it in the furnace to obtain an aluminum-fluorine co-doped ternary lithium positive electrode material.
[0048] (2) Aluminum-fluorine co-doped ternary lithium was used as the positive electrode material of the battery, mixed with conductive black (Super-P) and polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1, N-methylpyrrolidone (NMP) was added dropwise, ground into a slurry with a mortar, and the slurry was evenly applied to aluminum foil and dried in a vacuum oven for 12 hours. A button cell was assembled with aluminum foil as the positive electrode and lithium sheet as the negative electrode, and the performance of the battery was tested.
[0049] The results show that the performance of aluminum-fluorine co-doped ternary lithium positive electrode material is basically consistent with that of NCM811 material.
[0050] Example 5
[0051] (1) Take a mixed powder (2.0g of waste ternary lithium positive electrode powder + 0.10gLiOH, 0.05gLi2O and 0.05gLi2O2), raise the temperature to 400℃ at 5℃ / min under Ar atmosphere, and keep it for 2h; then raise the temperature to 850℃ at 5℃ / min, keep it for 12h, and cool it in the furnace to obtain the positive electrode material.
[0052] (2) The positive electrode material prepared by this method was mixed with conductive black (Super-P) and polyvinylidene fluoride (PVDF) in a ratio of 8:1:1, N-methylpyrrolidone (NMP) was added dropwise, and the mixture was ground into a slurry using a mortar. The slurry was evenly applied to aluminum foil and dried in a vacuum oven for 12 hours. A button cell was assembled with aluminum foil as the positive electrode and lithium sheet as the negative electrode, and the performance of the cell was tested.
[0053] The results show that the performance of the ternary lithium positive electrode material recycled and prepared by this method is lower than that of NCM, mainly because the material contains trace amounts of other impurities, which leads to a slight decrease in battery capacity.
[0054] Comparative Example 1
[0055] (1) Take a mixed powder (2.0g of waste ternary lithium positive electrode powder + 0.10gLi2O and 0.10gLi2O2), and in an Ar atmosphere, increase the temperature to 350℃ at 5℃ / min and keep it for 2h; then increase the temperature to 900℃ at 5℃ / min, keep it for 12h, and cool it in the furnace to obtain a doped ternary lithium positive electrode material.
[0056] (2) Aluminum-fluorine co-doped ternary lithium was used as the positive electrode material of the battery, mixed with conductive black (Super-P) and polyvinylidene fluoride (PVDF) at a ratio of 8:1:1, N-methylpyrrolidone (NMP) was added dropwise, ground into a slurry with a mortar, and the slurry was evenly applied to aluminum foil and dried in a vacuum oven for 12 hours. A button cell was assembled with aluminum foil as the positive electrode and lithium sheet as the negative electrode, and the battery performance was tested.
[0057] (3) The results show that the aluminum-fluorine co-doped ternary lithium positive electrode material prepared by this method does not contain fluorine in the EDX image of the recovered positive electrode material, and aluminum-fluorine co-doping is not achieved.
Claims
1. A method for preparing aluminum-fluorine co-doped positive electrode material using nickel-cobalt-manganese waste battery positive electrode material, characterized in that: The following steps are included: 1) mixing and ball-milling the positive electrode sheet obtained by stripping the waste nickel-cobalt-manganese battery with a lithium source to obtain a composite powder; the lithium source comprises lithium hydroxide; 2) The composite powder is calcined under a protective atmosphere to obtain an aluminum-fluorine co-doped positive electrode material.
2. The method for preparing aluminum-fluorine co-doped positive electrode material using nickel-cobalt-manganese waste battery positive electrode material according to claim 1, characterized in that: The mass proportion of lithium hydroxide in the lithium source is not less than 50%.
3. The method for preparing aluminum-fluorine co-doped positive electrode material using nickel-cobalt-manganese waste battery positive electrode material according to claim 2, characterized in that: The lithium source selectively comprises lithium oxide and / or lithium peroxide.
4. A method for preparing aluminum-fluorine co-doped positive electrode material using nickel-cobalt-manganese waste battery positive electrode material according to claim 1, 2 or 3, characterized in that: The mass of the lithium source is 5-10% of the mass of the positive electrode powder.
5. The method for preparing aluminum-fluorine co-doped positive electrode material using nickel-cobalt-manganese waste battery positive electrode material according to claim 1 or 2, characterized in that: The ball milling conditions are as follows: the ball milling medium is water and / or ethanol, the diameter of the grinding beads is 10 mm to 20 mm, the rotation speed is 30 to 60 rpm, the ball-to-material mass ratio is 3:1 to 8:1, and the ball milling time is 90 to 180 minutes.
6. A method for preparing aluminum-fluorine co-doped positive electrode material using nickel-cobalt-manganese waste battery positive electrode material according to claim 1 or 2, characterized in that: The calcination conditions are as follows: in a protective atmosphere, heating to 350-400°C at a heating rate of 3-5°C / min, keeping the temperature for 2-5h, then heating to 800-1000°C at a heating rate of 3-5°C / min, keeping the temperature for 10-15h, and cooling with the furnace.
7. The method for preparing aluminum-fluorine co-doped positive electrode material using nickel-cobalt-manganese waste battery positive electrode material according to claim 6, characterized in that: The protective atmosphere is at least one of nitrogen, argon, and nitrogen-argon.
Citation Information
Patent Citations
A method for recycling positive electrode materials from spent nickel-cobalt-manganese batteries.
CN108103323B
Recycling method of waste ternary fluorine-doped battery positive electrode material
CN113086996A
Cited By
Aluminum-fluorine-doped positive electrode material and preparation method thereof, positive electrode plate and battery
CN120319795A